Metode Pembelajaran Piano Di Purwacaraka Musik Studio Padang - Erick Setiawan; Erfan Erfan (SENDRATASIK UNP, 2020)
This study aims to describe how the piano learning methodsare used in Purwacara Music Studio Padang. It is seen in terms of objective, material, method, and evaluation. This research used a Qualitative approach which produced descriptive data about Piano Instruction in Purwacara Music Studio Padang.T he data were collected through observation, interview, documentation, and interactive data analysis consisting of data reduction, data presentation, and conclusion drawing. The results show that the piano learning process in Purwacara Music Studio is in accordance with the determined curriculum whose learning objective is students are able to play piano in right fingeringand sitting attitude. In the learning process, the methods implemented are lecture method, questions and answers, demonstration, drill, and assignment. Meanwhile, thelearning materialsare divided into two materials: music theory and music practice. In addition, evaluation is always held in every course meeting, and final evaluation as well as a test for improvement levelis held every 6 months. To get  more tangible and use fulbenefits, based onthe results of research and discussion about piano instruction in Purwacara Music Studio, forming a special team for designing piano learning materials in an guidebook is a suggestion the writer gives. This is due to the fact that available materials are not neatly arranged in a guidebook. Thus, the existence of the arranged materials in a guidebook can further enhance the process of learning.